2016
DOI: 10.1093/jxb/erw358
|View full text |Cite|
|
Sign up to set email alerts
|

PgLOX6encoding a lipoxygenase contributes to jasmonic acid biosynthesis and ginsenoside production inPanax ginseng

Abstract: HighlightIn ginseng, jasmonic acid promotes expression of the biosynthetic genes for ginsenosides. PgLOX6 encodes a lipoxygenase that is required for biosynthesis of jasmonic acid and its overexpression increases ginsenoside levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 50 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…In addition, eight lipoxygenase were also up-regulated in PS. Previous studies indicated that lipoxygenase is the first key enzyme in the synthesis pathway of jasmonic acid, which plays an important role in the germination, growth, and stress resistance of plant seeds (Rahimi et al, 2016 ). GIGANTEA, a gene involved in circadian clock and phytochrome signaling (Cha et al, 2017 ), was down-regulated in PS (Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, eight lipoxygenase were also up-regulated in PS. Previous studies indicated that lipoxygenase is the first key enzyme in the synthesis pathway of jasmonic acid, which plays an important role in the germination, growth, and stress resistance of plant seeds (Rahimi et al, 2016 ). GIGANTEA, a gene involved in circadian clock and phytochrome signaling (Cha et al, 2017 ), was down-regulated in PS (Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the plant diets containing the soybean prooxidant enzyme lipoxygenase (LOX) (initiating various oxygenated compounds production) led to retarded Manduca sexta larval growth, the insect pest of plants from the family Solanaceae. Second, wounds induced by WCM feeding on barley leaves could stimulate releasing of fatty acids from membrane lipids such as linolenic acid and next LOX could convert linolenic acid to jasmonic acid and further volatile aldehydes can be produced (Mosblech et al 2009 ; Rahimi et al 2016 ). This would be consistent with the above postulated role of arginase in the production of polyamines and stimulated by them the emission of volatiles.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PLA and LOX , which mainly appear in the leaf, may make major contributions to the accumulation of total ginsenosides in the leaf. PgLOX6 , which encodes a lipoxygenase, contributes to JA biosynthesis and ginsenoside production in P. ginseng and provides a molecular tool for increasing ginsenoside production (Rahimi et al, 2016). However, the expression of JA-related genes in the xylem remains low, indicating that the xylem should be a component of the JA transport system, but is not central to JA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%